Scalable photonic network architecture based on motional averaging in room temperature gas - J. Borregaard (Nature Portfolio, 2016)
Cold atomic ensembles have been considered suitable platforms to realize quantum memories, but their scalability is limited by the cooling apparatuses. Here, the authors show how room temperature atomic microcells can be used for discrete variable ensemble-based quantum information processing.